Characteristics of the bacterial microbiome in association with common intestinal parasites in irritable bowel syndrome. Issue 6 (June 2018) - Krogsgaard, Laura Rindom; Andersen, Lee O'Brien; Johannesen, Thor Bech; Engsbro, Anne Line; Stensvold, Christen Rune; Nielsen, Henrik Vedel; Bytzer, Peter
Abstract : Objective: : A low prevalence of intestinal parasites has been identified in individuals with irritable bowel syndrome (IBS), but potential associations with alterations in the bacterial microbiome remain largely unexplored. We aimed to investigate the relationship between parasites and bacteria in individuals with IBS in order to identify potential transkingdom microbial characteristics. Design: : Stool samples were collected from the Danish background population classified into IBS ( n = 119), unspecific gastrointestinal (GI) symptoms ( n = 114), and asymptomatic controls ( n = 186) based on the Rome III criteria for IBS. Bacterial (16S) and eukaryotic (18S) ribosomal DNA was sequenced, and 18S data were merged with data from conventional parasite laboratory tests. The bacterial microbiome was analyzed according to symptom group and parasite colonization status. Results: : Bacterial richness and diversity were similar for IBS and controls but higher in those with unspecific GI symptoms. A higher abundance of Bacteroides and a lower abundance of Faecalibacterium were detected in individuals with IBS and unspecific GI symptoms compared with controls. Principal component analyses indicated differences in bacterial composition related to parasite colonization rather than symptom group. Parasites were detected at the lowest frequency in the IBS group (39%) and in samples dominated by Bacteroides. Higher bacterial richness and diversity were found in parasite‐positive samples from controls and those with unspecific GI symptoms but not in individuals with IBS. Conclusion: : Parasite colonization, rather than bacterial composition, differed between individuals with IBS and healthy controls. Parasite colonization was associated to a rich and diverse bacterial microbiome; however, this association was altered in IBS.